MODA BUS KE MODA KERETA API JURUSAN SURABAYA – MOJOKERTO - Widyastuti, Hera; Buana, Cahya; Istiar, Istiar; Herijanto, Wahju; Kartika, Anak Agung Gde; Arif, Catur; Raharjo, Budi; Solikhah, Ummatus; Prabawati, Aldila Riana (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Under the terms of the capacity, the railway mode is more efficient in terms of moving passengers and goods as to accommodate more passengers and goods than bus modes. Moreover, when there are obstacles in the road such as road maintenance progress, and hole on the road, flooding, existence of demonstration and others, bus modes will not be able to serve passenger well. However in terms of mobility and flesibility the bus is more flexible than the train because it hasn’t limited by the schedule The government started to build new tracks to reduce the delay in the arrival of trains and increase the frequency of train departures. The new tracks are expected to make better services for passengers and goods. Under these conditions, they need to do research on the possibility displacement modes of transportation on passengers. Stated Preference technique used to obtain data on the willingness of passengers to switch modes by distributing questionnaires to Surabaya-Mojokerto line passengers. Those questionnaire are distributed in three terminals which are Joyoboyo Terminal (Surabaya), Purabaya Terminal, Bungurasih (Sidoarjo), and Kertajaya Terminal (Mojokerto). The obtained data were analyzed using Binary Logistic Regression. The result shown that respondent who spent 45 minute willing to move from bus to train is 27,13% whilst 60 minute is 48,10%. Considering the money spending of the respondent each time travel using bus in which stated as Rp. 15.000 it’s only 12,02% who are willing to move from bus to train.